Augmented reality application for chemical bonding based on android - Alexander Setiawan; Silvia Rostianingsih; Timotius Reinaldo Widodo (International Journal of Electrical and Computer Engineering (IJECE), 2019)
Augmented Reality can provide information that can be more easily understood by the user. Because of its advantages, Augmented Reality can be utilized to create learning applications that can support teaching and learning process. Chemical learning about chemical reactions is usually boring by students. This is because students only know the theory of the book and the explanation of teachers only. This research utilized Augmented Reality to be able to see 3D model of each chemical element and also can see animation of merging between elements. In order to bring up 3D objects of chemical elements then made a card that will be used as a marker / tracker. In addition, there can be a combination of several chemical elements based on several cards detected from the camera. The test is performed for chemical elements with periodic table such as H, Ca, Na, K, C, Cl, Br, O, S, SO2, CO2, OH. Testing the application by performing several merge elements such as HCl, NaCl, H20, CO2, MgS, SO2, O2, CaCl2, HCN, N2, and others. The results of this study will be tested on several students to see the benefits of student learning.